2022
DOI: 10.1186/s12929-022-00855-6
|View full text |Cite
|
Sign up to set email alerts
|

Oligo-Fucoidan supplementation enhances the effect of Olaparib on preventing metastasis and recurrence of triple-negative breast cancer in mice

Abstract: Background: Seaweed polysaccharides have been recommended as anticancer supplements and for boosting human health; however, their benefits in the treatment of triple-negative breast cancers (TNBCs) and improving immune surveillance remain unclear. Olaparib is a first-in-class poly (ADP-ribose) polymerase inhibitor. Oligo-Fucoidan, a low-molecular-weight sulfated polysaccharide purified from brown seaweed (Laminaria japonica), exhibits significant bioactivities that may aid in disease management.Methods: Macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…Although several studies have revealed the paradoxical role of AMPK in carcinogenesis, it has been found that activated AMPK is negatively associated with the development of breast cancer [52,53]. Similarly, we also found that upon the cytotoxicity of IPyA, AMPK in the breast cancer cells was evidently activated accompanying with dramatic reduction of ATP production, and the downstream (mTOR and ULK) was also affected.…”
Section: Discussionsupporting
confidence: 62%
“…Although several studies have revealed the paradoxical role of AMPK in carcinogenesis, it has been found that activated AMPK is negatively associated with the development of breast cancer [52,53]. Similarly, we also found that upon the cytotoxicity of IPyA, AMPK in the breast cancer cells was evidently activated accompanying with dramatic reduction of ATP production, and the downstream (mTOR and ULK) was also affected.…”
Section: Discussionsupporting
confidence: 62%
“…These earlier observations are extended herein by the identification of unique EpCAM + /CD44v6 + cellular neighborhoods that border NOS2/COX2 high regions. Given that EpCAM and CD44v6 are markers of metastasis and cancer stemness, these observations support the role(s) of tumor NOS2/COX2 expression key targets of disease progression in breast and other tumors (27,29). Moreover, the orthogonal expression of tumor NOS2/COX2 in distinct cells and regions within the TME suggest that the spatial configuration of these enzymes has important roles during intercellular communication.…”
Section: Discussionsupporting
confidence: 59%
“…38 Another study revealed that reduced EGFR activity was associated with the repolarization of macrophages from the M2 phenotype to the M1 phenotype in TNBC. 39 EGFR augments glycolysis in TNBC cells, and the combination of a glycolysis inhibitor and an EGFR inhibitor effectively reduces TNBC cell proliferation. 40 In addition, EGFR inhibitors have been reported to improve neuropathic pain in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that EGFR activation caused an increase in BRAC cell migration and invasion 38 . Another study revealed that reduced EGFR activity was associated with the repolarization of macrophages from the M2 phenotype to the M1 phenotype in TNBC 39 . EGFR augments glycolysis in TNBC cells, and the combination of a glycolysis inhibitor and an EGFR inhibitor effectively reduces TNBC cell proliferation 40 .…”
Section: Discussionmentioning
confidence: 99%